Glucose – a Reducing Sugar? Reducing Properties of Sugars in Beverages and Food - Kunz, Thomas; Lee, Eon-Jeong; Schiwek, Victoria; Seewald, Thorsten; Methner, Frank-Jürgen (BrewingScience, 2011)
The properties of reducing sugars are interesting for the shelf life of beverages, particularly beer, and for human nutrition. For the brewing process the different reducing potentials and the mode of action of fermentable sugars are vitally important, especially during wort boiling where the reactions of sugars are accelerated. Additionally, several breweries use non-fermentable sugars in the brewing process to imbue the beer with unique flavour, body and mouthfeel. An optimised method to ascertain the reduction potential of sugars against Fe3+ at low pH was developed in this work.